2019
DOI: 10.1097/cm9.0000000000000368
|View full text |Cite
|
Sign up to set email alerts
|

Spreading of extended-spectrum β-lactamase-producing Escherichia coli ST131 and Klebsiella pneumoniae ST11 in patients with pneumonia

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 58 publications
4
10
0
1
Order By: Relevance
“…Despite the fact that TEM and SHV variants are the most universal ESBLs, it seems that they have become less common over the past decade than CTX-M. The results of this study were consistent with previous studies that found the bla CTX-M gene as the most widespread ESBL type in K. pneumoniae isolates 16,17,25 . However, Ferreira et al 10 from Brazil and Carvalho et al 18 from Portugal showed a higher prevalence of bla SHV compared to bla CTX-M in K. pneumoniae, which was in contrast to our finding.…”
Section: Discussionsupporting
confidence: 90%
“…Despite the fact that TEM and SHV variants are the most universal ESBLs, it seems that they have become less common over the past decade than CTX-M. The results of this study were consistent with previous studies that found the bla CTX-M gene as the most widespread ESBL type in K. pneumoniae isolates 16,17,25 . However, Ferreira et al 10 from Brazil and Carvalho et al 18 from Portugal showed a higher prevalence of bla SHV compared to bla CTX-M in K. pneumoniae, which was in contrast to our finding.…”
Section: Discussionsupporting
confidence: 90%
“…ST11 international high-risk clone, the most prevalent sequence type in this collection, has been described in outbreaks of ESBL-producing K. pneumoniae in some countries such as Iran, China, Sweden and detected in a OXA-48-producing isolates from Iran and Spain [2,11,22,23]. In our study, ST11 co-carried multiple resistance determinants such as bla CTX−M−15, bla TEM , bla SHV and PMQR genes including qnrB, qnrS, oqxA, oqxB and aac(6)-Ib-cr, that correlates well with earlier reports as the dominant global ESBLs are the CTX-M type beta-lactamases in K. pneumoniae [2,22]. The presence of quinolone resistance genes aac(6′)Ib-cr and qnrB was recently reported in ST11 K. pneumoniae strains from Colombia [24].…”
Section: Discussionmentioning
confidence: 95%
“…Interestingly, our findings revealed Klebsiella pneumonia as the indicator of CAP LRTI patients using random forest classifier, which got an AUC value of 0.804. Studies have showed that Klebsiella pneumonia are the important pathogens causing pneumonia, which are associated with high morbidity and mortality [ 50 , 51 ]. In wheezing episodes in children, Klebsiella pneumoniae are predictive markers for the prediction of wheeze [ 52 ].…”
Section: Discussionmentioning
confidence: 99%